The effect of multiball training on the speed of target strokes forehand and stroke backhand drive in table tennis athletes at PTM Pade Angen Mataram NTB Tahun 2024 - fikri ramadhan (JOETAL: Journal of Education, Teaching and Learning, 2024)
The focus of the problem in this study is that this research is motivated by the low speed of the target strokes forehand and stroke backhand drive . table tennis at PTM Pade Angen Mataram NTB in 2024   Table Tennis Athletes. The research objectives to be achieved based on the formulation of the problem that has been defined are as follows: To find out whether there is an effect of multiball training on the speed of target strokes forehand and stroke backhand drive  in table tennis athletes at PTM Pade Angen Mataram NTB Tahun 2024 . The research design used was  experimental  research using a  Two group pretest-posttest  design.  In  this experiment there were  external variables that  influenced the  formation  of the dependent  variable.  Instruments  Accurate  target  speed  forehand  and  stroke backhand drive  table tennis techniques Sampling using a population study of 12 players divided into two groups. Based on the results of the research and data analysis above, it can be concluded that on this basis the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted N-1 (12- 1) =  11. After getting the t-count, target speed training forehand strokes - count > t-table, namely (3,995 > 1,796), and stroke backhand drive  exercise that t-count > t-table, namely (4,015 > 1,796). Based on the above facts, namely t-count is greater than t-table, thus the t-value obtained in this study is significant (influence). Ha (accepted) there is an effect of multiball training on target speed of forehand strokes in table tennis athletes at PTM Pade Angen Mataram NTB Tahun 2024 .